A five year financial plan for Emerson Network Power, Inc - Gerardo, Michelle Ann C., Macalaba, Rafael S., Amon, Rose Dama A., Duran, Sandra L., Auirre, Reillet Mae L., Kabiling, Christine Joy V., Pablo, Carla Mae S., Sena, Jason Vincent,. 4 0 16; 5 (2017)
EXECUTIVE SUMMARY This study is designed to create a financial plan of Emerson Network Power. The financial problem is mainly focused on the incapability of th entity to collect its receivable on time. The analysts used a five-year audited financial statements of the entity from 2011 to 2015 to make a financial analysis of the entity's problem. After carefully studying both internal and external environment of the entity, the financial rtios and historical data of the entity through their financial statements, the analysts come up to have three alternative courses of action. These are accounts receivable factoring, Establishment of Online Collection system and Granting of Trade Discounts. Among these three courses of action, the analysts decided that Establishment of Online Collection system is the best suited course of action to implement based on the financial problems they have in the entity. With the use of forecasted financial statements of the entity, the analysts projected the financial statements of the entity after employing the selected course of action. The course of action used by the analysts was able to increase cash inflow of the entity by 25%, decrease receivables by 7% in the 5-year span while also controlling costs snd cutting it by 5%. This lead to an increase in the entity's efficiency ratios: inventory turnover to 6xm wguc us 60 days and Accounts Receivable turnover by 2.5x equivalent to 145 days within the year span.
Thesis: (BSBA Major in Finance and Treasury Management) - Pamantasan ng Lungsod ng Maynila, 2017.
Keywords: 2 -- 0; 6; 20; 20; 2